Roles of transient receptor potential channels in regulation of vascular and epithelial barriers. Issue 2 (3rd April 2017) - Weber, Evan W.; Muller, William A.
ABSTRACT: Transient receptor potential (TRP) channels are a ubiquitously expressed multi-family group of cation channels that are critical to signaling events in many tissues. Their roles have been documented in many physiologic and pathologic conditions. Nevertheless, direct studies of their roles in maintain barrier function in endothelial and epithelia are relatively infrequent. This seems somewhat surprising considering that calcium ion concentrations are known to regulate barrier function. This short review provides an introduction to TRP channels and reviews some of the work in which investigators directly studied the role of TRP channels in endothelial permeability to electric current, solute, or leukocytes during the inflammatory response.